The Concept of Arabic Language and its Development in Tarbiyatu Muallim?n Al-isl?m? Prenduan - Kirom, Abdul; Ainin, Moh.; Rosyidi, Abdul Wahab (Universitas Al-Amien Prenduan, 2023)
This scientific research aims to characterize and promote the Arabic language at the Institute of Islamic Teacher Education in Burandwan. The researcher used a descriptive qualitative research methodology through interviews, observation, and documentation. So you get the fact that the Arabic language and its promotion in that institute are divided into two stages, the first of which is the foundation stage and the second is the implementation and promotion stage. Establishment stage: This stage goes back to the time of the founding of this institute in the year 1971 AD, with the efforts of Kayahi Haj Muhammad Idris Johari, hand in hand with Kayahi Hajj Muhammad Tijani Johari, who improved the sound structures and correct methods after coming from Mecca (1989 AD) until this stage was achieved with the title Success and paving the way in educating and teaching the Arabic language. The implementation and promotion stage: The process of the Arabic language as a language of communication and teaching may accelerate teacher education to its maximum extent for its employees, until the implementation and promotion stage has become as if it were facilitated in an instant, and elements of a) building a solid Arabic language teaching entity were formed in this stage, b) sending some distinguished cadres. And their enrollment in universities in Mecca and Medina in the Arabic language specialization, c) The large number of teachers who excel in the Arabic language and are effective in the fields of teaching it, d) Managing the implementation of linguistic and Arabic activities and educating them outside the classroom, e) The effectiveness of the linguistic and Arabic teams in forming cadres who excel in the Arabic language.